Fish Abundance, Diversity, and Identification in Jebba Lake (Journal of Environmental Bioremediation and Toxicology, 2023)
This study was carried out to determine the fish composition, diversity and abundance of the Jebba Lake. Three fishing communities were used for these studies (Fakun, Gbajibo and New-Awuru). During the study period, a total of 141 fishes comprising 19 species from 12 families at Fakun, 258 fishes with 22 species from 11 families at Gbajibo and 319 fishes with 38 species from 15 families at new Awuru were recorded. Fish were procured from artisanal fishermen and middlemen at landing sites on the lake. The collected fish samples were sorted and identified to families, genera and species levels, using the identification keys. The identified species were weighed to the nearest 0.1 g using a weighing balance and total and standard lengths were determined to the nearest 0.1mm using a measuring board and recorded on the data record sheet. Description statistics were used to calculate the total number and percentage weight of the species. The families included Mochokidae and Mormyridae, has the highest diversity in all three stations with six (6) species each, followed by Alestidae with five (5) species while Clariidae and Clarotidae have four (4) species each, Bagridae, Cichlidae and Schilbeldae with three (3) species each, follow by Cyprinidae with two (2) species and the least families are Citharinidae, Distichodontidae, Osteoglossidae, Tetraodontidae with one (1) species each. This makes a total of seven hundred and eighteen (718) fishes, forty (42) species and fifteen (15) families in all three stations. Fish species in Nigerian lakes are invaluable as bioindicators and biomarkers for environmental and food security research. They provide critical insights into the health and quality of aquatic ecosystems, helping to detect pollution, assess ecological integrity, and guide conservation efforts. Continued research and monitoring using fish bioindicators and biomarkers are essential for sustainable water resource management in Nigeria.
Keywords: Diversity; Identification key; Abundance; Artisanal Fishermen; Jebba Lake